Perspective of Rice Farmers Agricultural Extension Services - Ansyah, Ibnu Febri; Muksin (Jurnal Manajemen Agribisnis dan Agroindustri, 2025)
Agriculture is an important sector for many rural people. Agriculture has become the main daily livelihood and has many cultural dimensions that live in society. The dynamics of natural farmers developing their businesses are very directly related to the role of extension workers. This study aims to determine the quality of rice farmer extension services in Balung sub-district using the Servqual (Service Quality) method. The method is to identify and prioritize consumer satisfaction. The dimensions used in this study are Reliability, Responsiveness, Assurance, Empathy and Physical Evidence. The research was carried out for a quarter of more than 3 months. This research was conducted at the location of Agriculture in Balung District. The questionnaire was distributed to 60 farmer respondents in Balung District using the Simple Random Sampling technique. Based on the results of the study, it can be concluded that: (1) there are 8 items that are considered unqualified and unsatisfactory, the rest have been considered satisfactory. (2) From the dimensions of Reliability, Responsiveness, Assurance, Empathy and Physical Evidence, only the service in the dimension of Responsiveness is considered very satisfactory by the farmers. Meanwhile, the dimensions of Reliability, Guarantee, Empathy and Physical Evidence of the service still need to be improved because there are still several items in each dimension that are still not in accordance with the expectations of farmers. The role of extension workers is very important and has a sustainable impact on the progress of agriculture in a region. Farmers consider the existence of extension important